A decision support system for determination of a sustainable pit limit. (10th January 2017) - Rahmanpour, Mehdi; Osanloo, Morteza
Abstract: There is an increasing interest among practitioners to incorporate sustainability issues in evaluating the projects. However, it is a complex task to deal with the conflicting aspects of sustainable development. Nowadays, most of the minerals are produced by surface mining methods; where the economic, social and environmental impacts of these operations are closely related to Ultimate Pit Limit (UPL). UPL actuates the amount of mineable reserves, stripping ratio, location of waste dump and tailings dam, and the area of lands that will be disturbed at the end of a mining operation. Therefore, it has a significant contribution on the sustainability of the mining community. UPL determination is a strategic decision and it requires a Decision Support System (DSS) to evaluate and understand the outcome of each design alternative for optimal decision-making. In this DSS, after recognizing the indicators, it benefits from a matrix method to assess and measure the sustainability of different UPL alternatives based on subjective judgments. Moreover, some future information is unavailable and imprecise. In that regard, fuzzy logic is used to resolve uncertainties. Sungun Copper Mine data is used to show the effect of considering sustainability issues in UPL determination. The selected UPL changes net present value (NPV) and the mine life by 7% and 13 years respectively compared to the case where just economic issues are considered. The system shows to be efficient in assessing the sustainability issues of design alternatives during the feasibility studies.